2000
DOI: 10.1074/jbc.m003434200
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Carrier Protein-2 Alters High Density Lipoprotein-mediated Cholesterol Efflux

Abstract: were increased 48% and 115%, respectively, in SCP-2-expressing cells. Concomitantly, the level of the lipid droplet-specific adipose differentiation-related protein decreased 70%. Overall, HDL-mediated sterol efflux from L-cell fibroblasts reflected that of the cytoplasmic rather than lipid droplet compartment. SCP-2 differentially modulated sterol efflux from the two cytoplasmic pools. However, net efflux was determined primarily by inhibition of the slowly effluxing pool rather than by acceleration of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(153 citation statements)
references
References 57 publications
11
142
0
Order By: Relevance
“…The significance of the above findings in living cells was confirmed with DHE and other fluorescent sterols in a variety of cultured cells including L-cells, CHO cells, macrophages, and hepatocyte derived cell lines (39,43,45,160,(174)(175)(176). Studies with transfected L-cells showed that uptake and efflux of fluorescent sterols was highly dependent on the expression of cholesterol binding proteins (e.g.…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 66%
See 4 more Smart Citations
“…The significance of the above findings in living cells was confirmed with DHE and other fluorescent sterols in a variety of cultured cells including L-cells, CHO cells, macrophages, and hepatocyte derived cell lines (39,43,45,160,(174)(175)(176). Studies with transfected L-cells showed that uptake and efflux of fluorescent sterols was highly dependent on the expression of cholesterol binding proteins (e.g.…”
Section: Physiological Significance Of In Vitro Studies With Dhe and mentioning
confidence: 66%
“…SCP-2, ADRP) or their real-time uptake, distribution, and efflux dynamics in living cells. One exception is 22-NBD-cholesterol which has been shown to be not only bound with high affinity (nM K d s) by SCP-2 and ADRP, but with orientation within the binding site similar to cholesterol-suggesting that this probe may be suitable for study of intracellular cholesterol trafficking (4,(39)(40)(41)(42)(43)(44). Indeed, 22-NBDcholesterol has proven useful for real-time imaging of HDL-mediated cholesterol uptake, efflux, and intracellular trafficking in living cells such as L-cell fibroblasts as well as rat macrophages and lymphocytes (43,45,46).…”
Section: Advent Of Fluorescent Sterolsmentioning
confidence: 99%
See 3 more Smart Citations